A teoria do reconhecimento de Axel Honneth e a ampliação da justiça multiportas : uma proposta de atendimento sistêmico no contexto filosófico social - Velinho, Rochel Teresinha da Silva (2022)
This research discusses how Axel Honneth's theory of recognition can contribute to the applicability of the method of family constellations to the legal field, and whether, based on intersubjective recognition, it is possible to give visibility to social conflicts that emerge from family conflicts and thus expand the Multi-door Courthouse. For this purpose, this study proposes a philosophical theoretical foundation based on Hegel's concepts to validate a social philosophical systemic method for the use of family constellations in court, which, in addition to complying with the constitutional principles linked to the legal system in force, will fulfill a need in social relations, whose beneficiaries are the individuals and the society in legal relations, through a paradigmatic systemic approach and not therapeutic systemic modeling.